2015
DOI: 10.9734/air/2015/13932
|View full text |Cite
|
Sign up to set email alerts
|

The Constructivist Approach of Solving Word Problems Involving Algebraic Linear Equations: The Case Study of Mansoman Senior High School, Amansie West District of Ghana

Abstract: This paper is an action research which involves a sample of forty (40) second year students of Mansoman Senior High School. The study was aimed at using the constructivist approach to enhance students' competence in solving word problems involving algebraic linear equations. Prior to the study, it was observed that the students were not able to understand and solve word problems under algebraic linear equations. The constructivist approach of teaching and learning was employed as the intervention strategy and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 7 publications
(10 reference statements)
4
14
0
Order By: Relevance
“…According to the constructivism principle, students are not only passively acquiring information but are actively generating new knowledge based on previously acquired knowledge in combination with new experiences, thereby enhancing their performance [6]. Constructivism has changed the concept of teaching and learning to a more progressive way through which fresh ideas of the learners are brought to class, understood and strengthened by a range of teaching and learning strategies that actively involve them [6]. That suggests, therefore, that a constructivist approach to learning builds on the learner's natural innate abilities [19].…”
Section: Concept Of Constructivismmentioning
confidence: 99%
See 3 more Smart Citations
“…According to the constructivism principle, students are not only passively acquiring information but are actively generating new knowledge based on previously acquired knowledge in combination with new experiences, thereby enhancing their performance [6]. Constructivism has changed the concept of teaching and learning to a more progressive way through which fresh ideas of the learners are brought to class, understood and strengthened by a range of teaching and learning strategies that actively involve them [6]. That suggests, therefore, that a constructivist approach to learning builds on the learner's natural innate abilities [19].…”
Section: Concept Of Constructivismmentioning
confidence: 99%
“…From Chamot et al [5], learning to understand well enough to decode concepts found within a word problem is now a prerequisite for mathematical problem solving. 'Mathematical word problems, or story problems, have long been a common aspect of school mathematics,' according to [6]. Burton [7] stated that transformation of word problems into arithmetic or algebra creates considerable difficulty for many students, and from a psychological point of view a number of studies have discussed the linguistic and mathematical origins of that difficulty.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…And in addition to the active discussion, students are kept involved in the lesson and the teacher has a chance to continually monitor students' understanding of the concept being taught. In furtherance, teaching should be done in a way of allowing students to wonder why things are, to inquire, to search for a solution and to resolve incongruities and not teachers acting as the custodian of knowledge [12]. Classroom management represents a sizable obstacle to most teachers of today.…”
Section: Original Research Articlementioning
confidence: 99%